Approximate Solutions of the Generalized Two-Dimensional Fractional Partial Integro-Differential Equations - Fadhel, Fadhel S; Asker, Batool I (Al-Nahrain Journal of Science, 2019)
In this article, the existence’ and uniqueness’ theorem of the solution of the generalized two dimensional ‘fractional’ partial integro-differential equations (2DFPIDEs) have been proved. Then, the sequence of approximate solutions of the generalized 2DFPIDEs employing the variational iteration method (VIM) had been derived and proved and then we prove its convergence to the exact solution. Finally, illustrative examples are simulated using computer software Mathcad 15 and then a comparison between the approximate results and ‘the exact solution are given’, which discover its competence.